Site-selective oxidation of monolayered liquid-exfoliated WS2 by shielding the basal plane through adsorption of a facial amphiphile - Grieger, Sebastian; Szydłowska, Beata Maria; Rao, Vaishnavi J.; Steinmann, Eva; Dodds, Marcus; Gholamvand, Zahra; Duesberg, Georg S.; Zaumseil, Jana; Backes, Claudia (Angewandte Chemie. International edition, 2020)
In recent years, various functionalization strategies for transition-metal dichalcogenides have been explored to tailor the properties of materials and to provide anchor points for the fabrication of hybrid structures. Herein, new insights into the role of the surfactant in functionalization reactions are described. Using the spontaneous reaction of WS2 with chloroauric acid as a model reaction, the regioselective formation of gold nanoparticles on WS2 is shown to be heavily dependent on the surfactant employed. A simple model is developed to explain the role of the chosen surfactant in this heterogeneous functionalization reaction. The surfactant coverage is identified as the crucial element that governs the dominant reaction pathway and therefore can severely alter the reaction outcome. This study shows the general importance of the surfactant choice and how detrimental or beneficial a certain surfactant can be to the desired functionalization.